Evaluasi Kepuasan Pelanggan Aplikasi Spotify Berdasarkan Customer Satisfaction Index (CSI): Studi Kasus Pengguna di Indonesia - Rudolfo Rizki Damanik; Ronald Belferik; Chandra, Wenripin; Rosyadi, M. Dedy; Aulia Rizky Muhammad Hendrik Noor Asegaff (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
This study aims to measure customer satisfaction with the Spotify application using the Customer Satisfaction Index (CSI) method. Customer satisfaction is a crucial aspect for service providers to understand in order to improve product quality and competitiveness. Data were collected through questionnaires distributed to active Spotify users from various demographics. After data collection, validity and reliability tests were conducted using SPSS to ensure the accuracy of the research results. The analysis shows that Spotify's customer satisfaction level falls into the very satisfied category, with a CSI score of 87.39%. This finding indicates that the majority of users feel that Spotify meets or exceeds their expectations in terms of functionality, service quality, and ease of use. This study provides important insights for Spotify to maintain and improve customer satisfaction through continuous service enhancements. In conclusion, user satisfaction with Spotify is relatively high, and these research results can serve as a reference for the company in formulating strategies for future service improvements.